Fiscal stimulus for demand shock in Indonesia during the Covid-19 pandemic: Issue 1 No. 1 2022 - Ernawati, Ernawati; Ningtyas, Rita Ayu (Adpebi Science Series, 2022)
The Covid-19 pandemic has brought about economic shocks, prompting an economic contraction. The government carried out a fiscal stimulus for the economy to survive. This study aims to examine Indonesia's fiscal stimulus policy during the Covid-19 pandemic. The research data is sourced from the Indonesian Ministry of Health, the Statistic Indonesia, the Ministry of Finance, and the Financial Services Authority. The analysis was carried out using descriptive statistics presented in tables and graphs. The comparison is made for regional growth of the expenditure component between provinces with the highest Covid-19 cases and others. The study results show that the cases of Covid-19 infection are not related to the economic contraction depth because it depends on the dominant output structure of a province. Bali was the province with the highest demand shock resulting from the tourism sector's slowdown, which triggered a decrease in derived demand, such as transportation, hotels, restaurants, and other products or services. The demand side of fiscal policy is lower than the supply side. Funds for the recovery of the tourism sector are allocated as the sector most impacted during the Covid-19 pandemic.